Comparison of environmental indicators of two aviaries for laying Hens - Vitorasso, G. [UNESP]; Pereira, Danilo Florentino [UNESP]; Magalhães, M. M. de [UNESP]; Kakimoto, S. K. (My University, 2008)
The aim of this paper is to compare the environmental indicators of two housing systems for laying hens. The roof of aviary I was built with cement-asbestos tile, ridge vent, and long eaves. The roof of aviary 2 was built with clay roof tile. Both aviaries had suspended cages. The experiment took place in the city of Bastos, with latitude 21°57'30″ south, longitude 50°42'05″ west, and altitude 450 m, climate type CWA, with dry winter, according to Koppen classification. The experiment was done from March to May of 2007. The environmental indicators measured were: air temperature (T), ammonia concentration (AC), relative air humidity (RH), air speed (AS), noise (dB), roof temperature (RT), and brightness (Lux). These variables were measured at the central point within each aviary. The data was recorded during four non-consecutive weeks. Therefore, different environmental conditions could be compared. Aviary 2 had the highest values for air speed and air temperature. It had the lowest brightness and the lowest roof temperature. Considering the relative air humidity, it's not possible to reject the null hypothesis of equality for the medians between the aviaries. For both of them, the ammonia concentration was insignificant (AC<1 ppm). Differences were only observed between the aviaries related to the level of noise during the first two weeks: the highest values were found in aviary 2. The level of noise was lower during the first two weeks compared to the last two weeks for both aviaries. The study of environmental conditions allowed observation of significant differences between aviaries, reinforcing the importance of the region characteristics and aviary housing system when choosing architectural design, roof, and coverage material.
Keywords: Environment; Roofing material; Rural buildings; Agriculture; Ammonia; Architectural design; Atmospheric temperature; Building materials; Clay minerals; Housing; Moisture; Air humidities; Air speed; Air temperatures; Ammonia concentrations; Central points; Clay roof tiles; Environmental conditions; Environmental indicators; Null hypothesis; Roofs